Shape dynamics : relativity and relationalism - Mercati, Flavio (Oxford, United Kingdom : Oxford University Press, 2018)
Shape Dynamics is a radical yet soundly based reinterpretation of Einstein's theory of gravity that has opened up new approaches to gravity research. This text offers both a brief introduction and a detailed walk-through of the motivations for the theory, its development from first principles and an in-depth look at its present status.
"This textbook on the nature of space and time explains the new theory of Space Dynamics, which describes the dynamics of gravity as the evolution of conformal 3-dimensional geometry. Shape Dynamics is equivalent to Einstein's General Relativity in those situations in which the latter has been tested experimentally, but the theory is based on different first principles. It differs from General Relativity in certain extreme conditions. Shape Dynamics allows us to describe situations in which the spacetime picture is no longer adequate, such as in the presence of singularities, when the idealization of infinitesimal rods measuring scales and infinitesimal clocks measuring proper time fails. This tutorial book contains both a quick introduction for readers curious about Shape Dynamics, and a detailed walk-through of the historical and conceptual motivations for the theory, its logical development from first principles and a description of its present status. It includes an explanation of the origin of the theory, starting from problems posed first by Newton more than 300 years ago. The book will interest scientists from a large community including all foundational fields of physics, from quantum gravity to cosmology and quantum foundations, as well as researchers interested in foundations. The tutorial is sufficiently self-contained for students with some basic background in Lagrangian/Hamiltonian mechanics and General Relativity."--
Part I : historical motivation -- Newton's bucket -- Origins of the Mach -- Poincare principle -- Part II : Relational particle dynamics -- Barbour-Bertotti best matching -- Best matching : technical details -- Hamiltonian formulation -- Part III : Relational field theory -- Relativity without relativity -- York's solution to the initial-value problem -- A derivation of shape dynamics -- Cotton-squared theory -- Part IV: Shape dynamics -- Historical interlude -- Shape dynamics and the linking theory -- Solutions of shape dynamics.
Online resource; title from PDF title page (EBSCO, viewed March 12, 2018).
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Relativity (Physics); Gravitation; Astrodynamics; Gravitation; Relativité (Physique); Gravitation; Astrodynamique; TECHNOLOGY & ENGINEERING -- Engineering (General); Astrodynamics; Gravitation; Relativity (Physics); Electronic books